Sustainability in Heritage and Urban Planning - Della Spina, Lucia; Pellegrini, Paola; Russo, Antonia; Valluzzi, Maria Rosa; Viglianisi, Angela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume 'Sustainability in Heritage and Urban Planning' represents an extraordinary collection of papers spanning a broad spectrum of topics at the intersection of sustainability and heritage in urban planning. These articles included here are intellectually stimulating and vital in our contemporary context. From adaptive reuse of cultural landscapes to passive strategies in vernacular architecture, and from commercial culture's impact on urban structures to sustainable management of historic greenery, these articles cover a wide spectrum of crucial subjects. Each article contributes unique insights to the fields of architecture, heritage, urban planning, and sustainability. Explore these articles and join the conversation on shaping our built environment and cultural heritage.